Why and how investors use ESG information: evidence from a global survey - Amel-Zadeh, A; Serafeim, G (Chartered Financial Analysts Institute, 2018)
Using survey data from mainstream investment organizations we provide insights into why and how investors use reported environmental, social and governance (ESG) information. Relevance to investment performance is the most frequent motivation followed by client demand, product strategy, and then ethical considerations. Important impediments to the use of ESG information are the lack of reporting standards. Among the different ESG investment styles, negative screening is perceived as the least investment beneficial and is driven by product and ethical considerations while full integration and engagement are considered more beneficial and are driven by relevance to investment performance.